D04 Young people's experiences of finding out about a family history of Huntington's disease. (16th November 2010) - Keenan, K F; van Teijlingen, E; McKee, L; Miedzybrodzka, Z; Simpson, S A
Abstract : Background: How young people find out about a family history of Huntington's disease (HD) is important because disclosure experiences influence young people's coping mechanisms, family relationships and future decision making. While a growing body of research has explored family communication about genetic disease, little is known about young people's experiences. This poster presents findings from a recently published article which documents how young people find out about a family history of HD. Methods: In depth interviews were undertaken with 33 participants (aged 9–28 years). The interviews explored how and when young people find out, different modes of family communication and any impact on family relations. Young people were recruited through the North of Scotland regional genetics clinic and the Scottish Huntington's Association. Results: A qualitative inductive analysis revealed four types of disclosure experiences: (1) having always been told, (2) told gradually, (3) HD was kept a secret or (4) HD as a new diagnosis. The impact of different parenting styles and forms of family communication, as well as one's stage of awareness, were fundamental in structuring participant's accounts. Conclusions: Those children and young people who live with, or have close contact with, a parent or grandparent affected by HD want to know 'what is wrong?' and can cope with knowing 'at least something about the illness' from an early age. Our findings highlighted triggers which brought Huntington's and one's personal risk to the forefront of participant's attention, and identifies key times at which young people may need further information and support.